Management of Productive Zakat in the Development of Micro, Small and Medium Enterprises (MSMEs) at the National Baznas of Bulukumba Regency - Syahidah Rahmah; Nurhalisa Natasya (Jurnal Ar-Ribh, 2022)
The purpose of this study was to determine the management of productive zakat in Baznas Bulukumba Regency. The type of research conducted is qualitative research. Data obtained from informants with 10 informants. Data collection methods used in this study were observation, interviews and document studies in which the author saw firsthand the state of the field. The results of the research obtained by the author are that the management at the Bulukumba National Baznas is guided by the Standard Operating Procedure or commonly called (SOP) which has been set to facilitate the management process, so there is an assessment. Having the mechanism of a design or pleaning before entering the names of the mustahiks so that what the mustahik's needs are balanced. Some of the mustahik who have received zakat assistance from the Bulukumba Regency Baznas are still stagnant, but some have changed from a mustahik to a muzakki.